Complete mitogenomes characterization and phylogenetic analyses of Ceratophyllus anisus and Leptopsylla segnis - Liu, Yafang; Chen, Bin; Lu, Xinyan; Jiang, Dandan; Wang, Tao; Geng, Ling; Zhang, Quanfu; Yang, Xing (Frontiers in Veterinary Science, 2023)
Fleas are one of the most common ectoparasites in warm-blooded mammals and an important vector of zoonotic diseases with serious medical implications. We sequenced the complete mitochondrial genomes of Ceratophyllus anisus and Leptopsylla segnis for the first time using high-throughput sequencing and constructed phylogenetic relationships. We obtained double-stranded circular molecules of lengths 15,875 and 15,785 bp, respectively, consisting of 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNAs, and two control regions. AT-skew was negative in both C. anisus (-0.022) and L. segnis (-0.231), while GC-skew was positive in both (0.024/0.248), which produced significant differences in codon usage and amino acid composition. 13 PCGs encoding 3617 and 3711 codons, respectively, Isoleucine and Phenylalanine were used most frequently. The tRNA genes all form a typical secondary structure. Construction of phylogenetic trees based on Bayesian inference (BI) and maximum likelihood (ML) methods for PCGs. The results of this study provide new information for the mitochondrial genome database of fleas and support further taxonomic studies and population genetics of fleas.